Immunosenescence Psychosocial and Behavioral Determinants - Bosch, Jos A.; Phillips, Anna C.; Lord, Janet M. (Springer New York : Imprint: Springer, 2013)
This book presents the first multi-disciplinary approach to the understanding of immune aging, or immunosenescence; it combines biological data and clinical observations with psychological, social, and behavioral perspectives and is thus a valuable and timely contribution to the literature in this area.  Contributors, all eminent scholars in their respective fields, review thoroughly the state of the art in research that examines how psychological and behavioral factors influence the rate and extent of immune system aging.